Do Our Adolescents Know They Are Cyberbullying Victims?. (2nd January 2019) - Shakir, Taaha; Bhandari, Nehal; Andrews, Angela; Zmitrovich, April; McCracken, Courtney; Gadomski, Johnna; Morris, Claudia R.; Jain, Shabnam
ABSTRACT: Social media (SM) use is widespread among adolescents, and many SM outlets lend themselves to cyberbullying and its consequences, including anxiety, depression, and even suicide. The purpose of this study is to determine the current prevalence of bullying on SM and identify its sociodemographic characteristics. The survey is on SM use and cyberbullying of patients ages 12–18 at a large pediatric emergency department (ED) (April to June 2015) and a separate group of adolscents 11–19 years old at a school (October to November 2015). Data were analyzed using descriptive statistics. A total of 539 surveys were collected. The median age was 14 years; 57.7% of respondents were female. Additionally, 91.4% of respondents used SM, most commonly Instagram and text messaging. While 16.3% reported being bullied on SM, 40.6% reported experiencing cyberbullying (receiving mean or threatening emails or negative comments); 56.4% knew someone who had been bullied on SM. Anxiety was higher in victims of SM bullying compared with nonvictims (44.5% vs. 17.1%), and 86.5% of cyberbullies had also experienced cyberbullying. Of those who had been bullied, only 19% wanted to stop using SM. We concluded there is underrecognition of bullying on social media. Although its use is associated with anxiety and depression, adolescents don't want to stop using SM. Given high SM use by adolescents, there is an urgent need for education and possible screening tools for this "new world" entity.